2020
DOI: 10.1111/cge.13896
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the role of extrachromosomal DNA in tumor pathogenesis and evolution

Abstract: The amplification of oncogenes on extrachromosomal DNA (ecDNA) provides a new mechanism for cancer cells to adapt to the changes in the tumor microenvironment and accelerate tumor evolution. These extrachromosomal elements contain oncogenes, and their chromatin structures are more open than linear chromosomes and therefore have stronger oncogene transcriptional activity. ecDNA always contains enhancer elements, and genes on ecDNA can be reintegrated into the linear genome to regulate the selective expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Using our cell line model, we further discover that ecDNA can provide more elevated copy numbers than HSR due to the lack of a centromere leading to unequal segregation at cell division, suggesting a more pivotal role of ecDNA in adapting to selective pressures from cancer therapy. Previous studies have shown that ecDNA may dynamically relocate to chromosomal HSR [ 5 , 33 ]. Other studies also found that HSR may promote the formation of ecDNA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using our cell line model, we further discover that ecDNA can provide more elevated copy numbers than HSR due to the lack of a centromere leading to unequal segregation at cell division, suggesting a more pivotal role of ecDNA in adapting to selective pressures from cancer therapy. Previous studies have shown that ecDNA may dynamically relocate to chromosomal HSR [ 5 , 33 ]. Other studies also found that HSR may promote the formation of ecDNA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The behavior and structure of ecDNAs are different between various cancer types [ 94 , 95 ]. EcDNAs lead to tumor heterogeneity and drug resistance by promoting the amplification of oncogenes [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Intratumoral Heterogeneitymentioning
confidence: 99%
“…Although its significance is rapidly gaining recognition, the role of extrachromosomal DNA (ecDNA)—circular DNA constructed from nucleosomal chromatin—in cancer is less well characterized. ecDNA has been identified as a major carrier of amplified oncogenes ( 1 ), and it is more open than chromosomal DNA, resulting in increased transcriptional activity ( 2 ). Owing to its lack of a centromere, ecDNA is inherited in a non-Mendelian pattern during mitosis ( 3 ), resulting in some tumour cells carrying high copy numbers of oncogenes that can substantially influence tumor heterogeneity and drug resistance ( 4 ).…”
Section: Introductionmentioning
confidence: 99%